A extinção dos efeitos dos atos administrativos em virtude do descumprimento de deveres pelo destinatário: a cassação e seu regime jurídico - Gimenez, Décio Gabriel (2010)
The purpose of the present work is to comprehend one of the hypotheses of extinction of the effects caused by administrative acts, such as that one which results from the non-compliance by the addressee of obligations identified in the Brazilian Law. This hypothesis deserves a specific treatment, once it is submitted to a peculiar law regime, resultant of its qualification as administrative sanction. Therefore, the administrative act has been contained within the realm of administrative function, drawn afterwards to an overview of the hypotheses of its extinction and under a dogmatic methodological perspective, in order to identify and detach, among the kinds of State declarations with revoking efficiency, that one which has as presupposition the practice of an imputable administrative illicit to the addressee of the act, henceforth called cassation act. Moreover, this work aims to identify, taking the structural focus of the administrative act and the juridical regime that regulates the edition of administrative sanctions, what are the limits to the edition of the State declarations here discussed. To reach this purpose, this study approaches the object, the fundaments, the presupposition and the juridical effects of the cassation act. Finally, this work also treats the control of this kind of administrative act, focusing the actions exerted by the Judiciary